Cases on learning design and human performance technology - Stefaniak, Jill E., 1984- (Advances in human resources management and organizational development (AHRMOD) book series., 2020)
"This book examines relevant cases that demonstrate how principles of learning design and human performance technology have been employed within organizations. It also addresses business problems, quality improvement initiatives, and business opportunities"--